HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA KAKI DENGAN KETEPATAN SHOOTING PADA SISWA EKSTRAKURIKULER SEPAKBOLA SMAN 1 KAMPAR KABUPATEN KAMPAR - Azhariyadi, Benny; Juita, Ardiah; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s of football extracurricular student in SMAN 1 Kampar, research found the result of shooting football was not optimal. Leg-eyes coordination also need when shooting ball, this influences the low of explosive power leg muscles and the low leg-eyes coordination. The purpose of this research is to see the correlation of explosive power leg muscle with the accuracy of shooting, the correlation leg-eyes coordination with the result shooting and the coordination explosive power leg muscles and leg-eyes coordination with the accuracy of shooting of football extracurricular of 1 Kampar Senior High School. Population in this research is all football extracurricular students of SMAN 1 Kampar amount 22 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 22 people. Research instrument used vertical jump test, leg-eyes coordination and the result of shooting. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : 1. Shows that there is correlation of explosive power leg muscle with the accuracy of shooting which shows correlation rhitung (0,509)> rtabel (0,433) at α=0,05o. 2 there is correlation leg-eye coordination with the accuracy of shooting, which shows correlation rhitung (0,443)> rtabel (0,433) at α=0,05. 3. There is correlation between explosive power leg muscles and leg-eyes coordination with the accuracy of shooting, which shows rhitung (0,567)> rtabel (0,433) .Key word : explosive power leg muscles, leg-eyes coordination and shooting.